Mortality in Metropolises of Ukraine: Historical Parallels with the Study of Yu. O. Korchak-Chepurkivsky - Ryngach N. О. (Statistics of Ukraine, 2021)
The purpose of this paper is to make a comparative analysis (find historical parallels) of the situation with mortality causes in four cities of Ukraine in 1923–1929 and in our time, by comparing the mortality structure in 1926 and 2019, to identify structural changes and make assumptions regarding their determinants. Based on data from statistical tables of mortality in the four largest cities of the Ukrainian Socialist Soviet Republic (Kyiv, Kharkiv, Dnipropetrovsk, and Odessa) for 1923–1929 and data from the State Statistics Service of Ukraine for 2019 on the distribution of deaths by death cause in the same cities and in Ukraine, the structural shares by main classes were calculated (according to the current classifications). Changes in the contribution of various causes of death to the mortality of the urban population are estimated. The overall progress (the advancement of medical science and practice, the improvement of living conditions (including sanitation and hygiene) and quality of life, the increased population’s awareness of health issues and access to medical care, etc.), immunization programs, the development and production of effective drugs have significantly reduced the mortality and transformed its structure. It is shown that the list of the leading causes, especially their ranks, given in the research of Yu. O. Korchak-Chepurkivsky, differed significantly from the analogous list for modern metropolises of Ukraine. In contrast to the situation in the four largest Ukrainian cities in 2019, with the majority of deaths caused by diseases of the circulatory system (about 65%), almost the same total share (67.4%) of deaths in the above cities in 1926 was determined by five classes (infectious or communicable diseases, diseases of the respiratory and digestive organs, cardiovascular diseases, and diseases of the nervous system and sense organs). The largest share of deaths in the four largest cities of the Ukrainian Socialist Soviet Republic was found to be caused by infectious and parasitic diseases (over 27%). Given that part of the infectious pathology (the diseases of the digestive system and nervous system in the first place) was registered by the then nomenclature in other classes, their contribution to the totality of deaths can be assessed as more significant (at least by 10–15%). The structural share of mortality from infectious and parasitic diseases in the four largest cities has decreased from 27% altogether to nearly 2%. There was a significant transformation in the spectrum of causes: while in 1926 high mortality was due to scarlet fever, whooping cough, typhoid fever and paratyphoid fever evolved to almost zero, in our time its significant part was caused by a new pathology, a disease caused by the human immunodeficiency virus (HIV). At the same time, the significance of tuberculosis as a cause of death is a striking difference between the mortality pattern in Ukrainian cities and the situation in modern developed countries. The decreased structural shares of infectious, respiratory and digestive diseases (some of which are also of infectious etiology), along with the prevalence of pathologies occurring in the perinatal period, congenital malformations, deformities and chromosomal abnormalities, were the largest changes in the infant mortality structure.